2022
DOI: 10.1055/s-0042-1744369
|View full text |Cite
|
Sign up to set email alerts
|

The Blending Effect of Single-Shade Composite with Different Shades of Conventional Resin Composites—An In Vitro Study

Abstract: Objectives Single-shade composite systems are gaining popularity among clinicians due to the claimed potential of blending with different tooth structure shades while restoring the tooth. The purpose of this study was to evaluate the blending effect of two single-shade composite with different shades of conventional resin composite systems. Materials and Methods Seventy-two composite cylinders of B1, B2, A1, A2, A3, or A3.5 shade from CharmFil Plus (CP) and Filtek Universal Restorative (3M) were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…It is considered one of the most widely researched singleshade material, with several research work investigating its color adjustment potential [6,9,[20][21][22], and optical properties [23,24]. The color stability of Omnichroma under accelerated aging conditions using Xenon Arc UV light sources to simulate exposure to natural sunlight [25] and 1 week staining in tea [26] were also investigated. In addition, its instrumental color adjustment potential was shown to improve after 1 month storage in distilled water [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered one of the most widely researched singleshade material, with several research work investigating its color adjustment potential [6,9,[20][21][22], and optical properties [23,24]. The color stability of Omnichroma under accelerated aging conditions using Xenon Arc UV light sources to simulate exposure to natural sunlight [25] and 1 week staining in tea [26] were also investigated. In addition, its instrumental color adjustment potential was shown to improve after 1 month storage in distilled water [27].…”
Section: Discussionmentioning
confidence: 99%
“…The color of a natural tooth is determined by a combination of the optical properties of dentin and enamel, 1 which results from the reflection and refraction of light on those tissues. 2 3…”
Section: Introductionmentioning
confidence: 99%
“…The color of a natural tooth is determined by a combination of the optical properties of dentin and enamel, 1 which results from the reflection and refraction of light on those tissues. 2,3 To mimic the chromatic harmony of the natural tooth, direct esthetic restorations have been made in layers with different resin composite masses with the same optical characteristics as natural enamel and dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Resin-based composites (RBCs) are widely used as direct restorative materials due to their versatility in different clinical scenarios, good mechanical properties, and excellent aesthetics [ 1 , 2 , 3 , 4 ]. Since nanotechnology was introduced in the manufacturing of dental RBCs, nanocomposites have demonstrated superior properties compared to their predecessors [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the immense advantages of using a one-shaded RBC in different clinical situations, a significant amount of research followed the introduction of OM on the market. The color and optical behavior of OM were intensely investigated in recent studies [ 4 , 5 , 9 , 12 , 13 , 14 , 15 , 16 ]. It was found that the filler system with supra-nanospherical particles demonstrated increased light transmission [ 17 ].…”
Section: Introductionmentioning
confidence: 99%